2010
DOI: 10.1111/j.1349-7006.2010.01653.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new oil adjuvant for use in peptide‐based cancer vaccination

Abstract: Vaccine therapies are increasingly being used for the treatment of various diseases, and the antigen molecules themselves are being expanded from whole microorganisms to fine molecules such as peptides. Accordingly, there is a need for new adjuvants to support these new applications. In this paper, we used pharmaceutical grade mineral oil and sorbitan monooleate to develop a new oil adjuvant formula, NH 2 , and investigated its effects on peptide vaccination at both the pre-clinical and clinical levels. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…12 Tat-interacting protein of 110 kDa (TIP110), which was initially cloned from a human KG-1 myeloid cell line cDNA library, 13 is implicated in RNA metabolism and tumor-antigen presentation. [14][15][16][17] We demonstrated previously that TIP110 regulates the transcription of HIV-1 and cellular genes. 18,19 It is considered a mammalian homolog of the yeast Prp24 protein, and functions as a general pre-mRNA splicing factor.…”
Section: Introductionmentioning
confidence: 99%
“…12 Tat-interacting protein of 110 kDa (TIP110), which was initially cloned from a human KG-1 myeloid cell line cDNA library, 13 is implicated in RNA metabolism and tumor-antigen presentation. [14][15][16][17] We demonstrated previously that TIP110 regulates the transcription of HIV-1 and cellular genes. 18,19 It is considered a mammalian homolog of the yeast Prp24 protein, and functions as a general pre-mRNA splicing factor.…”
Section: Introductionmentioning
confidence: 99%
“…NH 2 was extensively used as an adjuvant for peptide-based cancer vaccination and outperformed Montanide ISA 51 in the induction of a cellular immune response in mice. 44 The efficacy of the peptide-based vaccine adjuvanted by NH 2 was confirmed in phase-1 clinical trials with advanced cancer patients.…”
Section: Emulsionmentioning
confidence: 93%
“…Various other modifications of existing emulsion based delivery systems have promising future, e.g., NH 2 containing mineral oil and high purity oleic acid derivative, sorbitan monooleate. NH 2 being a w/o emulsion was able to protect encapsulated peptide antigen from peptidase and also provided a slow release of the peptide giving sustained antigenic stimulation [ 70 ]. Similarly a novel w/o/o multiple emulsion system containing squalene oil encapsulating peptide antigen gp100 was investigated for its efficacy as a vaccine delivery system for melanoma immunotherapy [ 64 ].…”
Section: Particulate Peptide Vaccine Delivery Methodsmentioning
confidence: 99%
“…Also, they elicited CTL response in presence of CPG (added as an adjuvant) and inhibited the growth of tumors in mice [ 72 , 73 ]. Induction of CTL response was also observed in liposomes surface decorated with peptides derived from a non-structural polyprotein in severe acute respiratory syndrome (SARS)-associated coronavirus [ 70 , 74 ]. In a similar study, hepatitis C virus derived peptides coupled to surface of liposomes were found to confer complete protection to immunized mice with the establishment of long term memory [ 72 , 75 ].…”
Section: Particulate Peptide Vaccine Delivery Methodsmentioning
confidence: 99%